PERBANDINGAN ZAKAT DAN PAJAK (IMPLEMENTASI RELIGIUSITAS ZAKAT DALAM PERPAJAKAN SEBAGAI UPAYA MENCEGAH TAX AVOIDANCE) - Anne Putri; Aries Tanno (FEB Universitas Sultan Ageng Tirtayasa, 2016)
Tax tax avoidance is a major problem faced by many countries. The government imposed sanctions clear to its citizens to ensure the implementation of tax payments. Unlike taxes which have clear and firm sanctions, lack of supervision and sanction the payment of zakat does not preclude the public to carry out their zakat obligation.Zakat and tax is a compulsory payment without any contra directly to the payer. The payment of zakat and taxes can be used to improve the welfare of the community. In general zakat equal to the zakat tax. Some experts said that charity is